Modelling of small CFRP aerostructure parts for X-ray imaging simulation. Issue 3 (12th August 2014) - Bliznakova, Kristina; Kamarianakis, Zacharias; Dermitzakis, Aris; Bliznakov, Zhivko; Buliev, Ivan; Pallikarakis, Nicolas
Abstract : Purpose: – The purpose of this paper is to develop a realistic computational model of carbon fibre reinforced polymer (CFRP) structures dedicated for in-silico investigations of the use of X-ray-based imaging techniques as non-destructive testing (NDT) of CFRP parts. Design/methodology/approach: – CFRPs contain layers of carbon-fibres bundles within resin. Bundles' orientation in the different layers is arranged with respect to each other at a well-defined primary direction. In the model, the bundle was simulated as a circular cylinder. The resulted model is a stack of layers of unidirectional bundles having orientation of 0°/90°/45°/−45°. Two CFRP structures were modelled: a flat CFRP part and a real shaped CFRP clip. A porous layer and non-carbon fibres were inserted within each model, respectively. X-ray projection images were generated with a dedicated simulation programme. Three setups were investigated: radiography, tomosynthesis and cone-beam CT (CBCT). Findings: – Results showed that porosity and non-carbon fibres were visible with all X-ray-based techniques. Tomosynthesis and CBCT, however, provide higher quality image of defects. Practical implications: – The CFRP computational model is a valuable tool in design, testing and optimization phase of X-ray-based imaging techniques for use in NDT of composite materials. Simulated images are generated within a short time; thus results from virtual optimization and testing are obtained very fast and at low cost. Originality/value: – An innovative computational model of CFRP structures, dedicated for X-ray imaging simulations, has been developed. The model is characterized by simplicity in its creation and realistic visual appearance of the produced X-ray images.